Integrated approach for the prediction of crack width and spacing in flexural FRC members with hybrid reinforcement - Taheri, Mahsa (2020)
In this paper, a new model is developed based on the moment-rotation approach to predict average crack width and average crack spacing of flexural elements made of fibre reinforced concrete (FRC) that also include longitudinal steel and/or fibre reinforced polymer (FRP) bars. The post-cracking behaviour of FRC is simulated by a stress-crack width relationship, while the interaction between concrete and longitudinal reinforcement is modelled by a multilinear shear stress-sliding diagram based on experimental evidence. For assessing the predictive performance of the developed model, an experimental program was executed with this type of structural elements, where the moment versus average crack width and crack spacing were recorded. The good predictive performance of the model was also demonstrated by using experimental results available in the literature. The predictive performance was, in general, better than the predictions from RILEM TC 162-TDF and fib Model Code 2010